Discernere Per Vivere Bene Il Proprio Tempo Proposta Educativa Alla Luce Degli Orientamenti Pastorali Di Papa Francesco = Discerning how to live in your time well : Educational proposal in the light of the pastoral guidelines of papa Francesco - Séïde, Martha (2018)
In the context of the Synod of Bishops on young people, with an interest to reflect on the times and spaces of education in contemporary society, this article aims at responding to the solicitations of Pope Francis to educate for discernment, thus accompanying young people to live their time well. This path implies, first of all, the awareness of the challenges of this time with the implications of "good living". Subsequently the concept of discernment is explained according to the pastoral orientations of Pope Francis. Finally, some guidelines of education for discernment focus on the verbs: recognizing, interpreting and choosing as a synthesis of the process of discernment. (English)
Keywords: Discernimento; Discernimiento; Discernment; choose; educar; educare; educate; elegir; Interpret; interpretar; interpretare; recognize; reconocer; riconoscere; scegliere; tempo-spazio; tiempo-espacio; time-space